Impact of pregnancy-induced hypertension on fetal growth (Medical Journal of Indonesia, 2016)
Background: Pregnancy-induced hypertension (PIH) is still a major cause of maternal and infant morbidity and mortality worldwide. The aim of this study to investigate the impact of PIH on fetal growth. Methods: A longitudinal cross-sectional study was conducted by 2,076 obstetric patients registered in the book of delivery emergency room BLUD RSUD Ende/ Ende hospital from September 1st 2014 to August 31st 2015. Pregnancy-induced hypertension was classified into gestational hypertension, preeclampsia, and severe preeclampsia. Categorical comparative chi-square continued by logistic regression analysis were performed to examine the effect of PIH to infants’ growth outcome. Results: Women with preeclampsia had higher number of preterm delivery (26.7%). Infants born from preeclamptic women had lower birth weight (median 2,575 gram; p<0.001), birth length (median 49 cm; p<0.001), and also head circumference (median 32 cm; p<0.001). Severe preeclampsia contributed statistically significance to SGA (OR=1.90; 95% CI=1.20-3.01; adjusted OR=1.91; 95% CI=1.20-3.01) and LGA (OR=2.70; 95% CI=1.00-7.29; adjusted OR=2.92; 95% CI=1.07-8.00). Based on birth weight independent of gestational age, severe preeclampsia had an impact to VLBW (OR=11.45; 95% CI=2.77-47.38; adjusted OR=8.68; 95% CI=1.57-48.04) and LBW (OR=6.57; 95% CI=4.01-10.79; adjusted OR=5.71; 95% CI=3.33-9.78) where it showed statistical significance. Conclusion: PIH women who had SGA or VLBL or LBW infants were caused by the hypoperfusion model as the pathogenesis of preeclampsia. Meanwhile, LGA infants born by preeclamptic women were due to the compensation of the decrease from uteroplacental perfusion or other diseases such as obese mother or gestational.diabetes mellitus.